PENERAPAN PENDEKATAN TEACHING AT THE RIGHT LEVEL TERHADAP PENINGKATAN HASIL BELAJAR BAHASA INDONESIA SISWA KELAS V DI SDN 024 TARAKAN - Saenab, Siti Arafah; Desy Irsalina Savitri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research was conducted to improve the learning outcomes of Indonesian language students in grade V at SD Negeri 024 Tarakan by applying a teaching at the right level approach. The research method used is classroom action research (PTK) and consists of 2 cycles. Each cycle consists of two meetings. The first meeting is used for planning, implementation, observation and reflection. Data processing in this study was carried out through observation and tests with research subjects totaling 20 students. The results showed that in cycle 1 without the implementation of TaRL, the number of students who completed 77.86% increased in cycle 2 by 91.92% against the learning process with the application of the TaRL approach, because they felt grouped according to their ability level. The implication of this study is that the TaRL approach can effectively improve the Indonesian learning outcomes of grade V students.